PHYTOSOCIOLOGICAL STUDY OF THE MONTANE FOREST ON THE SOUTH SLOPE OF MT. WILIS, EAST JAVA, INDONESIA - Purwaningsih Purwaningsih; Ruddy Polosakan; Razali Yusuf; Kuswata Kartawinata (BRIN Publishing (Penerbit BRIN), 2017)
PURWANINGSIH, POLOSOKAN, R., YUSUF, R. & KARTAWINATA, K. 2017. Phytosociological study of the montane forest on the south slope of Mt. Wilis, East Java. Indonesia. Reinwardtia 16(1): 31 - 45. —A phytosociological stud y of a montane forest was carried out on the south slope of Mount Wilis, Kediri, East Java. The objective of the study was to do quantitative measurements of floristic composition and structure of the montane forest located within the seasonally dry climatic region as to date no such study has been undertaken there. It was conducted using the quadrat method by establishing plots of 2500 m2 each at five locations at the altitudes of 1100 m asl (above sea level), 1200 m asl, 1300 m asl, 1400 m asl and 1500 m asl, thus the total area sampled was 1.25 ha. They were Plot1100 at Bekayang, Plot1200 at Bukit Bendera, Plot1300 at Batutulis, Plot1400 at Mergosepi and Plot1500 at Brak. A total of 1045 trees comprising 74 species of 50 genera and 33 families were recorded. Based on a species constancy index of 100 %, the Saurauia nudiflora-Weinmannia blumei association was established. The association consisted of (1) the Cyathea-Polycias subassociation, representing the heavily disturbed forest, currently dominated by Cyathea contaminans and (2) the Villebrunea-Syzygium subassociation, representing the least disturbed forests, dominated by Syzygium lineatum and Villebrunea rubescens. The lowest number of species (13) was recorded in Plot1100 and the highest number (39) in Plot1300. Important species recorded included Cyathea contaminans (Importance Value, IV= 47.97); Lithocarpus sp. (IV= 22.07); Lithocarpus sundaicus (IV= 14.05); Saurauia pendula (IV= 12.85); Villebrunea rubescens (IV= 12.12) and Syzygium lineatum (IV= 11.22). Diameter measurements showed that 76.60 % of trees in Plot1100 and 86.60 % in Plot1200 consist of small individuals with diameters between 10 and 30 cm. Trees with large diameters of >30 cm occurred in Plot1300, Plot1400 and Plot1500. The presence of large numbers of small trees and lesser numbers of trees with large diameters in a forest stand indicated that the stand was regenerating after heavy disturbance. The presence of the majority of trees with height of < 20 m (99 %) further confirmed the forest’s dynamic status.